FRI0198 Multi-Country, Cross-Sectional Study to Determine Patient-Specific and General Beliefs towards Medication and their Treatment Adherence to Selected Systemic Therapies in 6 Chronic Immune-Mediated Inflammatory Diseases (ALIGN). (10th June 2014) - Michetti, P.; Weinman, J.; Mrowietz, U.; Smolen, J.; Schremmer, D.; Tundia, N.; Gillas, F.; Selenko-Gebauer, N.
Abstract : Background: Adherence to therapy is critical to achieve and sustain management targets and optimal outcomes in treating patients (pts) with immune-mediated inflammatory disease (IMID). Pts' beliefs about the necessity of treatment and concerns about potential adverse effects could strongly influence adherence. However, knowledge about such beliefs and concerns in pts with IMIDs is quite limited. Objectives: Conduct a multi-country cross-sectional study exploring pts' beliefs, concerns, attitudes and adherence toward TNF inhibitors (TNFi) and selected conventional therapies used either alone or in combination across multiple IMIDs. Methods: In the ALIGN study, adults age ≥18 y diagnosed with rheumatoid arthritis (RA), ankylosing spondylitis (AS), psoriatic arthritis (PsA), Crohn's disease (CD), ulcerative colitis (UC) or psoriasis (PsO) who were receiving conventional therapy and/or disease-modifying antirheumatic drugs (including TNFi) were recruited by specialists at different disease stages. Pts completed validated questionnaires such as the Beliefs about Medicines Questionnaire (BMQ) and short Morisky Medication Adherence Scale (MMAS-4) at a single visit. Analyses of BMQ specific scores, MMAS-4 scores and pts' attitudes toward their medications are presented. Results: 7328 pts were recruited, including 7197 in 33 countries (Western Europe/Canada, 56.8%; Eastern Europe/Middle East, 19.8%; Latin America, 12.8%; Asia Pacific, 10.6%) who met eligibility criteria. Eligible pts had RA (27.5%), AS (11.3%), PsA (8.9%), CD (17.3%), UC (8.8%) or PsO (26.2%). Mean age was 47.5 y (range, 38.0 in CD to 54.8 in RA). Mean disease duration was 11.7 y (range, 8.1 in UC to 18.7 in PsO). The largest proportion of pts received conventional therapies (40.3%), followed by TNFi mono- (32.0%) and combination therapy (27.7%). An attitudinal analysis combining BMQ necessity and concern scores revealed that most pts were either "accepting" (high necessity/low concern) or "ambivalent" (high necessity/high concern) toward their medication irrespective of disease or treatment type. Adherence across disease types was generally higher in pts receiving TNFi with or without conventional therapy (range of mean MMAS-4 scores, 3.4–3.7; 0–1 = low adherence, 2–3 = medium adherence, 4 = high adherence), vs pts receiving conventional mono- (2.6–3.3) or combination therapy (2.8–3.4). Across all treatment types, high adherence according to MMAS-4 analysis was consistently lower among "ambivalent" pts (46.1–69.0%) vs "accepting" pts (55.8%−77.6%) according to combined BMQ scores (Table). Conclusions: Compared with "accepting" pts, "ambivalent" pts appeared to be less often highly adherent (MMAS-4 score=4), which could negatively affect treatment efficacy. The high percentage of "ambivalent" pts across disease types reveals the need to better explore pts' concerns about medication during routine consultations and to address any erroneous beliefs regarding benefit-risk of treatments to avoid potential nonadherence. Acknowledgements: AbbVie funded the study and the analysis, and approved the abstract for submission. Jennifer Han, MS, of Complete Publication Solutions, Horsham, PA, provided writing assistance. Disclosure of Interest: P. Michetti Grant/research support: MSD AG Switzerland, Consultant for: MSD, AbbVie, Abbott, UCB, Delenex, Vifor, Speakers bureau: MSD, UCB, Abbott, J. Weinman Employee of: Atlantis Healthcare, U. Mrowietz Grant/research support: Abbott/AbbVie, Almirall-Hermal, Amgen, BASF, Biogen Idec, Celgene, Centocor, Eli Lilly, Forward Pharma, Galderma, Janssen, Leo Pharma, Medac, MSD, Miltenyi Biotech, Novartis, Pfizer, Teva, VBL, Xenoport., Consultant for: Abbott/AbbVie, Almirall-Hermal, Amgen, BASF, Biogen Idec, Celgene, Centocor, Eli Lilly, Forward Pharma, Galderma, Janssen, Leo Pharma, Medac, MSD, Miltenyi Biotech, Novartis, Pfizer, Teva, VBL, Xenoport., Speakers bureau: Abbott/AbbVie, Almirall-Hermal, Amgen, BASF, Biogen Idec, Celgene, Centocor, Eli Lilly, Forward Pharma, Galderma, Janssen, Leo Pharma, Medac, MSD, Miltenyi Biotech, Novartis, Pfizer, Teva, VBL, Xenoport., J. Smolen Grant/research support: Abbott/AbbVie, Consultant for: Abbott/AbbVie, D. Schremmer Employee of: GKM Gesellschaft fuer Therapieforschung mbH, N. Tundia Shareholder of: AbbVie, Employee of: AbbVie, F. Gillas Shareholder of: AbbVie, Employee of: AbbVie, N. Selenko-Gebauer Shareholder of: AbbVie, Employee of: AbbVie DOI: 10.1136/annrheumdis-2014-eular.2030